Russian sign language: Main problems of vocabulary study - A.A. Komarova (Ученые записки Казанского университета: Серия Гуманитарные науки)
The article gives a brief description of the world's sign languages, i.e., of their features, genealogy, and status. It also considers possible approaches to studying the vocabulary of Russian sign language (RSL). Particular attention is paid to signs, which are currently of great interest to researchers, native speakers, and students learning RSL as a second language. Furthermore, they cause serious difficulties in translating them into other languages. In many cases, sign lexemes of RSL can be translated using Russian phraseological units. In different periods, various terms have been introduced to denote such sign lexemes: from idioms to non-equivalent vocabulary, multichannel signs, and language-specific vocabulary. The article analyzes the studies on this issue, starting with the works of G.L. Zaitseva from the 1990s to the present, as well as the classification of the vocabulary of sign languages by Russian and foreign specialists, including those used in cognitive linguistics. T. Johnson and L. Ferrara described the nature of some lexical signs as idiomatic and considered the concept of lexico-grammatical continuum and idiomaticity as the two properties of all sign languages. Here the features of RSL vocabulary are analyzed, examples of non-equivalent vocabulary are given, and it is proposed to consider RSL idioms as indivisible and integral combinations of two or more signs that perform the function of a single lexeme.